Case on Delivery Performance Improvement - Tengku Hasanul, Firdaus (Penerbit UMP, 2017)
The objective of this case study is to improve lead time delivery of spare parts from Distributor Center (DC) to TTT Sdn. Bhd. (TTT) warehouse which is located at Kemaman, Terengganu before deliver to end user within Kemaman area.